2015
DOI: 10.3390/su7066976
|View full text |Cite
|
Sign up to set email alerts
|

Balance of Comparative Advantages in the Processed Food Sector of the Danube Countries

Abstract: Abstract:In this paper, we investigated the level of competitiveness of the processed food sector of the Danube region countries, in order to show the existence of comparative advantage and the correlation of exports. We used the Balassa (RCA-revealed comparative advantage) index and TPI (trade performance indexes). At first, using the Pearson and Spearman index, we examined the existence of correlations between the processed food sector of the Danube countries. Then, we applied the Least Significant Differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 9 publications
2
19
0
1
Order By: Relevance
“…Such evidences are also confirmed by previous studies on competitiveness of Countries in the Danube regions. For example the study [23] concluded that "In the following commodity groups in Serbia an increase of positive comparative advantage is present: milk and products, except butter and cheese; butter and other fats from milk; dairy spreads, cheese and curd, products of cereals, flour, starch; vegetables, roots and tubers, processed; fruit prepared and products; sugar, molasses and honey; chocolate and other food preparations with cocoa". In another analysis [21] have been using D'Agostino and Pearson omnibus normality test showing that the Balassa index value distribution in Romania does not deviate significantly from normality (K2 = 2.46 and p = .29).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Such evidences are also confirmed by previous studies on competitiveness of Countries in the Danube regions. For example the study [23] concluded that "In the following commodity groups in Serbia an increase of positive comparative advantage is present: milk and products, except butter and cheese; butter and other fats from milk; dairy spreads, cheese and curd, products of cereals, flour, starch; vegetables, roots and tubers, processed; fruit prepared and products; sugar, molasses and honey; chocolate and other food preparations with cocoa". In another analysis [21] have been using D'Agostino and Pearson omnibus normality test showing that the Balassa index value distribution in Romania does not deviate significantly from normality (K2 = 2.46 and p = .29).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…According to research conducted [19,21,22], we performed a correlation analysis of the obtained indexes, to examine the extent to which the indices related to the identification of comparative advantages ( *Correlation is significant at the 0.05 level (2-tailed). **Correlation is significant at the 0.01 level (2-tailed).…”
Section: Comparative Advantage Of Honey Exports Of Serbia Romania Anmentioning
confidence: 99%
“…The authors Bozic and Nikolic (2013b) analyse the level of comparative advantages of Serbian agri-food sector on the global market and the major trading partners (the EU and the CEFTA member states), and the results show that the liberalization of the market led to certain changes in the comparative advantages of the agrarian sector. According to Ignjatijevic et al (2014), who analysed the level of international competitiveness of the processed food sectors for the countries of the Danube region, in Serbia there is an increase of competitiveness of the processed food sector measured by the revealed comparative advantages. Birovljev et al (2015) dynamically analysed the comparative advantages of the export of Serbian agri-food products in the regional countries, as well as the level of specialization in trade with these countries, and the doi: 10.17221/345/2015-AGRICECON results of their research showed that Serbia, although having the similar trade structure as the regional countries, owns comparative advantages in all regional countries, and as far as the level of specialization is concerned, in the most of the regional countries a high level of specialization is present.…”
Section: Doi: 1017221/345/2015-agriceconmentioning
confidence: 99%
“…Since the Danube region represents a potential basic and potential for the creation of a single market it is necessary to consider the level of competitiveness of the agricultural sector and take advantage of the development potential of the region. Achieving macro-regional competitiveness and regional coherence is important in strengthening international coperation (Ignjatijević et al, 2014).…”
Section: Introductionmentioning
confidence: 99%